Strategic Risk Management to Increase Profitability of Companies in the Tele-Communications Industry in Kenya - Wanjohi, Jemimah Mutunge; Omwenga, Dr. Jane (European Journal of Business and Strategic Management, 2017)
Purpose: The main purpose of this study is to establish the effect of strategic risk management and its role in increasing profitability in the tele-communications industry in Kenya. Methodology: The study used descriptive study design. Statistical package for social science (SPSS) aided data analysis. Regression model was fitted to check the relationship of the variables and presented in the form of frequency distribution tables, graphs and pie charts that facilitated description and explanation of the study findings. Findings: Results of the study showed that 57.9% of variation or change in the profitability of the firm is explained by; explained by the risk identification, risk assessment and communication, risk monitoring and evaluation and organization structures. This implies that these factors are very significant (since the p-values< 0.05) and therefore need to be considered as a strategy in implementation of profitability of the firm. Policy recommendation: The study recommends a standard risk assessment criterion through the implementation of well-defined policies. The study further recommends that the risk monitoring and evaluation should be a continuous process. Indeed a department should be set up for the role of risk monitoring and evaluation.